Midurethral Sling Removal or Revision in Women With Chronic Pain. Issue 9 (September 2022) - Rockefeller, Nicholas F.; Petersen, Timothy R.; Jeppson, Peter C.; Dunivan, Gena; Ninivaggio, Cara; Meriwether, Kate; Gallegos, Maxx A.; Komesu, Yuko M.
Abstract : (Abstracted from Female Pelvic Med Reconstr Surg 2022;28:e149–e153) Mesh midurethral slings (MUSs) have been the subject of extensive review and are considered surgically effective for treating stress urinary incontinence with favorable safety profiles. Mesh midurethral slings have known but uncommon complications including mesh exposure, pain, dyspareunia, and infection.